PENGARUH PENAMBAHAN KUBIS MERAH (Brassica oleraceae var.) TERHADAP AKTIVITAS ANTIOKSIDAN DAN TINGKAT KESUKAAN KONSUMEN PADA BISKUIT TEPUNG BIJI RAMBUTAN - Linda Ristiana; Nanik Suhartatik (Bioeksperimen: Jurnal Penelitian Biologi, 2015)
Rambutan seed flour could be utilized as a food especially as source of carbohydrate, fat, and protein. Red cabbage could be used as natural food color because of their anthocyanin content. The aims of the research were to investigate the effect of red cabbage to the antioxidant activity and consumer preference of rambutan seed flour biscuit. This research was use completed randomized design with 9 combinations and 2 replications. The results showed that the highest antioxidant activity was biscuit made by 50 g of rambutan seed flour addition and 20% of red cabbage extract, e.i 19.48 % radical scavenging activity (RSA) of DPPH. But biscuit which was most prefere by panel test was only 25 g of rambutan seed flour without any addition of red cabbage extract. Rambutan seed flour and red cabbage addition to the biscuit did affect the antioxidant activity and the consumer preference of the biscuit.